Effects of endogenous GIP in patients with type 2 diabetes. Issue 1 (21st May 2021) - Stensen, Signe; Gasbjerg, Lærke S; Krogh, Liva L; Skov-Jeppesen, Kirsa; Sparre-Ulrich, Alexander H; Jensen, Mette H; Dela, Flemming; Hartmann, Bolette; Vilsbøll, Tina; Holst, Jens J; Rosenkilde, Mette M; Christensen, Mikkel B; et al.
Abstract : Objective: The insulinotropic effect of exogenous, intravenously infused glucose-dependent insulinotropic polypeptide (GIP) is impaired in patients with type 2 diabetes. We evaluated the effects of endogenous GIP in relation to glucose and bone metabolism in patients with type 2 diabetes using a selective GIP receptor antagonist and hypothesized that the effects of endogenous GIP were preserved. Design: A randomized, double-blinded, placebo-controlled, crossover study. Methods: Ten patients with overweight/obesity and type 2 diabetes (mean±s.d. ; HbA1c 52 ± 11 mmol/mol; BMI 32.5 ± 4.8 kg/m 2 ) were included. We infused a selective GIP receptor antagonist, GIP(3-30)NH2 (1200 pmol/kg/min), or placebo (saline) during two separate, 230-min, standardized, liquid mixed meal tests followed by a meal ad libitum . Subcutaneous adipose tissue biopsies were analyzed. Results: Compared with placebo, GIP(3-30)NH2 reduced postprandial insulin secretion (Δbaseline-subtracted area under the curve (bsAUC)C-peptide % ± s.e.m. ; −14 ± 6%, P = 0.021) and peak glucagon (Δ% ± s.e.m. ; −11 ± 6%, P = 0.046) but had no effect on plasma glucose ( P = 0.692). Suppression of bone resorption (assessed by circulating carboxy-terminal collagen crosslinks (CTX)) was impaired during GIP(3-30)NH2 infusion compared with placebo (ΔbsAUCCTX ; ±s.e.m. ; −4.9 ± 2 ng/mL × min, P = 0.005) corresponding to a ~50% reduction. Compared with placebo, GIP(3-30)NH2 did not affect plasma lipids, meal consumption ad libitum or adipose tissue triglyceride content. Conclusions: Using a selective GIP receptor antagonist during a meal, we show that endogenous GIP increases postprandial insulin secretion with little effect on postprandial glycaemia but is important for postprandial bone homeostasis in patients with type 2 diabetes.